Preparation, Characterization, and Biological Evaluation of New Schiff Base Ligand and their Complexes with iron(II), cobalt(II), nickel(II) and Copper(II) Ions - Mohammed Hamid Said (Journal of Global Pharma Technology, 2016)
In the present work a new schiff  base ligand was prepared by reaction of 6-amino penicillinic acid with 5-chlorosalicyldehde. The new ligand was characterized by using various techniques UV/ Visible, FT IR , Mass spectral ,1H NMR, and 13C NMR , It was also preparing four new complexes by interaction of ligand with transition metals ions ( Fe2+, Co2+, Ni2+, Cu2+ ) and characterized by UV/ Visible, FT IR, Magnetic moment and  molar conductance. Ligand shows tridentate   behavior demonstrated by the presence of three effective groups and complexes have taken octahedral form. The biological effectiveness was measured  for ligand and coordination complexes  against two types of bacteria ( Staphyllococcus aureus and Pseudomonas aeruginosa ) showed good effectiveness.Keyword: β-Lactam, Schiff base, 6.Amino Penicillinic, and tridentate ligand.